Re: Reduction of Inflammatory RANTES/CCLS Serum Levels by Surgery in Patients with Bone Marrow Defects of the Jawbone [Letter] - Keith DA (Dove Medical Press, 2023)
David A Keith1,2 1Dental Section, Journal of Pain Research, Dove Medical Press, Auckland, New Zealand; 2Corresponding Member of the Faculty, Oral and Maxillofacial Surgery, Harvard School of Dental Medicine, Visiting Oral and Maxillofacial Surgeon, Massachusetts General Hospital, Boston, MA, USACorrespondence: David A Keith, Email dkeith@partners.org